2021
DOI: 10.1111/crj.13326
|View full text |Cite
|
Sign up to set email alerts
|

Validation of PSI/PORT, CURB‐65 and SCAP scoring system in COVID‐19 pneumonia for prediction of disease severity and 14‐day mortality

Abstract: Background The unprecedented COVID‐19 pandemic has put a serious burden on the healthcare system worldwide. Due to varied manifestations of SARS‐CoV‐2 infection, many scoring systems, which were earlier used for community acquired pneumonia (CAP) are in use to determine the disease severity and the need of ICU admissions for proper management. COVID‐19 is a relatively new disease and the validity of these scoring systems in SARS‐CoV‐2 infection is not completely known. This study aimed to validate these scorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…While many studies showed the PSI and CURB-65 systems to be beneficial in the assessment of COVID-19 severity and good predictors of mortality, some found other scoring systems better. SCAP score (Severe Community-Acquired Pneumonia) was found to be a more accurate marker of 14-day mortality (Anurag and Preetam, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While many studies showed the PSI and CURB-65 systems to be beneficial in the assessment of COVID-19 severity and good predictors of mortality, some found other scoring systems better. SCAP score (Severe Community-Acquired Pneumonia) was found to be a more accurate marker of 14-day mortality (Anurag and Preetam, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…While many studies showed the PSI and CURB-65 systems to be beneficial in the assessment of COVID-19 severity and good predictors of mortality, some found other scoring systems better. SCAP score (Severe Community-Acquired Pneumonia) was found to be a more accurate marker of 14-day mortality ( Anurag and Preetam, 2021 ). Another cohort found the COVID-GRAM score as the preferred means to identify patients with higher mortality with pneumonia caused by SARS-CoV-2 ( Esteban Ronda et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite in the early phase of pandemic several other COVID-19 and non-COVID-19 specific scores have been employed in an attempt to stratify according to mortality or ICU admission risk, validation studies failed to confirm their applicability in larger populations (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). According to a recent review article analyzing the existing scores predicting COVID-19 mortality, the 4C mortality score, designed specifically for COVID-19, is likely to have the best performance, though it has intrinsic limitations and a relatively low positive predictive value (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Wuhan, China, in December 2019, viral pneumonia has become a significant public health issue (1). The disease caused by this virus, called coronavirus disease 2019 (COVID-19), is characterized by a wide range of symptoms, from mild to severe, with acute respiratory distress syndrome being its main complication (2).…”
Section: Introductionmentioning
confidence: 99%
“…The disease caused by this virus, called coronavirus disease 2019 (COVID-19), is characterized by a wide range of symptoms, from mild to severe, with acute respiratory distress syndrome being its main complication (2). Therefore, assessing the severity of COVID-19 at the time of hospital admission acquired fundamental importance during the pandemic (1).…”
Section: Introductionmentioning
confidence: 99%